2020
DOI: 10.1002/ppul.25165
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus bronchiolitis, maternal asthma, and the development of asthma and lung function impairments

Abstract: Background: Children with a history of rhinovirus (RV) positive bronchiolitis have a high risk of developing subsequent asthma. Maternal asthma might also increase this risk. The aim of this study was to investigate the combined effects of hospitalization for RV positive bronchiolitis in infancy and a history of maternal asthma on the development of asthma at preschool age. Methods: This is a prospective cohort study of 139 preschool-aged children, with a history of hospital admission for bronchiolitis in infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…There were eight studies 9,10,17,22,40–42 and Makrinioti et al (https://doi.org/10.3389/falgy.2021.728389) investigating associations between RSV‐bronchiolitis and recurrent wheeze development as compared to RV‐bronchiolitis. All studies included in this meta‐analysis reported data for coinfections.…”
Section: Resultsmentioning
confidence: 99%
“…There were eight studies 9,10,17,22,40–42 and Makrinioti et al (https://doi.org/10.3389/falgy.2021.728389) investigating associations between RSV‐bronchiolitis and recurrent wheeze development as compared to RV‐bronchiolitis. All studies included in this meta‐analysis reported data for coinfections.…”
Section: Resultsmentioning
confidence: 99%
“…12 In our previous study, oscillometry-based outcomes at this followup suggested that the combined effects of RV infection and maternal asthma history were associated with increased airway resistance and reactance at preschool age. 14 Here we add to this evidence by showing lung ventilation inhomogeneities in those children with a history of hospital admission for RV bronchiolitis which are more apparent in those with a severe clinical course.…”
Section: Discussionmentioning
confidence: 65%
“…One hundred and thirty-nine children were followed-up at preschool age after bronchiolitis admission in infancy as described previously. 14 Technically acceptable MBW data were collected for 84 out of 103 (82%) participants who attempted MBW, and 60% of the overall cohort could be followed up. There were no differences in baseline characteristics between children in the total cohort (n = 139) and children with acceptable MBW measurements (n = 85) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy is a crucial period in determining the future health of the offspring [10] and hence, further understanding on mother's pregnancy health and children's respiratory and allergic diseases are necessary. To date several studies have shown that maternal asthma during pregnancy, pre-pregnancy obesity, and gestational weight gain are associated with an increased risk of asthma or wheezing in the offspring [12,[22][23][24]. However, most of these existing studies followed children from the first year of life to preschool or early school age [12,25].…”
Section: Introductionmentioning
confidence: 99%